Medical education and the importance of teaching medical teachers about teaching - Kent, Athol Parkes (Department of Health Sciences Education, 2018)
This is an overview of medical education today. It deals with tertiary education matters pertinent to medical schools in South Africa, the forces that will inevitably cause medical education to change and the responses of other countries to similar circumstances. These forces are medical, educational and political. The medical forces bringing about changes are concerned with the explosion in knowledge in the fields of medical facts, technologies, therapies and informatics. It is an ongoing educational problem as to how the burgeoning sciences can be balanced with the present call for the return to the humanities. Medical schools are being required, through their teaching and learning methodologies, to encourage the qualification of empathetic graduates with generalist (holistic) skills and attitudes to best serve their patients. Educational forces, in particular new curriculum strategies, will need to be explored to assist teachers and students to cope with the demands of communities and individuals for care with expertise. In many First World countries these demands have found expression in moves from Traditional to Innovative curricula. Fundamentally, Traditional schools teach normal Anatomy and Physiology first, then move to the abnormal, before students reach the Clinical Years where these "basic sciences" are applied. Innovative schools, on the other hand, employ Problem-Based Learning with Community-Orientation throughout their curricula, with early patient contact, horizontal and vertical integration of disciplines, group work and community interaction as crucial aspects of their students' learning. Supporters of the Innovative philosophy see as progressive the revising of Flexnerian notions of basic science building blocks, the debalkanising of instruction subject by subject and the motivational impetus achieved when learning takes place in context. Political factors can impinge on staff teaching and student learning by Governmental demands through statutory councils or through the power exerted by the universities. Macro politics dictate financial or other resources that are allocated and may in future directly influence what sort of doctor the various medical schools are expected to graduate. The politics of staffing the teaching institutions, the development of teachers, and the demographics of the student population raise important questions of direction and commitment, and may lead to new realignments. The recognition of the importance of teaching at a professional level is a crucial factor in educating students more appropriately. Teachers versed in the medical pedagogic process will be pivotal in producing a new breed of doctors. This new breed will not be expected to "know everything" but have a core knowledge carefully ascertained by each medical faculty and the ability to find information that is further required. Students will not be expected to acquire all the facts to sustain them through the rest of their professional lives, but to have enquiring minds and the motivation to continue their education, to satisfy their curiosity and provide improved patient care. Their skills in mastery of the behavioural sciences will be more pertinent than ever as preventative medicine becomes as important as curative. They will be expected to formulate ethical attitudes and provide leadership in community and individual dilemmas. These are challenges that will need to be faced critically by our medical teachers who are too often experts in content in ever-narrower sub-specialities. For these challenges to be met, teaching cannot be taken for granted, but must be viewed more seriously by the schools and changes made where appropriate. The University of Cape Town (UCT) has a considerable reputation in the quality of its medical graduates. However, for its medical faculty to remain in the forefront of medical education, it needs to reconsider the knowledge required, the skills and attitudes embodied in its graduates but, as importantly, it must take the lead in undergraduate training. The need for renewing strategies and the action required are the themes of this dissertation.